Radiological and biochemical resolution of nutritional rickets with calcium. Issue 9 (22nd August 2003) - Oginni, L M; Sharp, C A; Badru, O S; Risteli, J; Davie, M W J; Worsfold, M
Abstract : Aims: To determine the response to oral calcium in Nigerian children with rickets. Methods: In a teaching hospital in Western Nigeria, 26 children (13 boys, 13 girls, aged 2–5 years) with confirmed rickets received calcium lactate (2.7 g/day). Results: Within one month of treatment leg pain was relieved and the children were more active. The mean x ray score improved from 3.3 at baseline to 1.7 at three months and 0.9 at six months (arbitrary scoring system, 0–6). Twelve cases were healed radiologically after six months, 11 others improved considerably, two showed no significant improvement, and a non-compliant patient was worse. There was progressive reversal of biochemical features. Median plasma alkaline phosphatase fell from 519 (range 178–1078) to 283 (209–443) IU/l (p = 0.04) in four months, while mean 1, 25-dihydroxyvitamin D fell from 473 (251–1057) to 281 (155–481) pmol/l (p = 0.04), and mean plasma calcium increased from 2.26 (1.63–2.54) to 2.37 (2.06–2.54) mmol/l (p = 0.13). Parathyroid hormone fell from 5.3 (0.4–21.5) to 1.7 (0.45–7.4) pmol/l. Type I collagen carboxy terminal cross linked telopeptide was very high at baseline (20 (7.2–103) to 14 (11–24) μg/l) (p = 0.03) and fell promptly to normal. Conclusion: Calcium supplementation alone effected healing of rickets in most of these Nigerian children and may provide sufficient treatment in this environment.